Shiga Toxin-Producing Escherichia coli in Finland from 1990 through 1997: Prevalence and Characteristics of Isolates - Keskimäki, Markku (American Society for Microbiology, 1998)
During the past 10 years Shiga toxin-producing Escherichia coli (STEC) has emerged as one of the most important causes of food-borne infections in industrialized countries. In Finland, with a population of 5.1 million, however, only four STEC O157:H7 infections were identified from 1990 through 1995; the occurrence of non-O157 STEC infections was unknown. In 1996, we established a national prospective study to determine the prevalence of STEC serotypes in feces of Finns with bloody diarrhea. During this enhanced 1-year study period eight sporadic cases of STEC infection were found; of them, only two were indigenously acquired O157:H7 infections. In 1997, O157 infections increased dramatically, with O157 strains causing 51 of all 61 STEC infections. Altogether 14 non-O157:H7 STEC strains were found in Finland in the 1990s: O26:H11 (four strains), O26:HNM (HNM indicates nonmotile), O2:H29, O91:H21, O91:H40, O101:HNM, O107:H27, O157:HNM, O165:H25, OX3:H21, and Rough:H49. All O157:H7 and O26:H11 isolates produced enterohemolysin, but seven of the other STEC strains did not. Most (n = 63) of the 71 STEC strains isolated carried the stx(2) gene only, five carried the stx(1) gene only, and three carried both genes. The eaeA gene was detected in all other isolates except five non-O157 strains. There were seven distinct pulsed-field gel electrophoresis (PFGE) genotypes among 57 O157 strains and three distinct PFGE types among four O26:H11 strains. The main PFGE type was found among 65% of all O157 isolates.